Employee competencies as predictors of organizational performance: A study of public and private sector banks - Salman, M.G., Showkat, A.and Saleem, I. (Management and Labour Studies)
Drawing on the resource-based view, this paper seeks to examine the influence of employee competencies on organizational performance using a sample of 325 managerial and non-managerial employees working in Indian public and private sector banks. The study employed a cross-sectional research design, and the data were collected through a structured questionnaire using convenience sampling. Confirmatory factor analysis was used to check the reliability and validity of the dimensions, and the proposed hypotheses were tested by using structural equation modelling. The results indicated a positive and significant impact of selected employee competencies on organizational performance except for self-competence, which showed an insignificant and negative effect. The study is of immense potential to help policy and decision-makers of the Indian banking industry to develop and implement strategies for improving employee competencies, which, in turn, are instrumental in enhancing organizational performance. This study is a unique attempt to examine the impact of various employee competence dimensions on organizational performance, particularly in the Indian banking industry. - Reproduced
Keywords: Banks, Employee competencies, India, Organizational performance, Structural equation modelling